Development of records management system for matriculation colleges in Malaysia - Rosnizam Eusoff; Zawiyah M. Yusof (Penerbit UKM, 2011)
An efficient and effective records and information management is essential to avoid problems which could cause operational failure. A records management system has been developed for selected matriculation colleges in Malaysia. A survey was initiated in order to identify the needs and justify the development of such a system. Survey method, employing questionnaire as the technique to collect data was adopted. The questionnaires were distributed to 120 respondents from October 2009 through February 2010. The return rate is 85.8% (103). The collected data was descriptively analysed using Statistical Package for Social Science (SPSS) version 16.0. Rapid Application Development (RAD) was used in the system development process. User acceptance test (UAT) was conducted to measure the acceptability of the system. The result of the test indicates the potential usage of the system in matriculation colleges throughout Malaysia.